Snake Venom PLA2s Inhibitors Isolated from Brazilian Plants: Synthetic and Natural Molecules. (22nd September 2013) - Carvalho, B. M. A.; Santos, J. D. L.; Xavier, B. M.; Almeida, J. R.; Resende, L. M.; Martins, W.; Marcussi, S.; Marangoni, S.; Stábeli, R. G.; Calderon, L. A.; Soares, A. M.; Da Silva, S. L.; et al.
Abstract : Ophidian envenomation is an important health problem in Brazil and other South American countries. In folk medicine, especially in developing countries, several vegetal species are employed for the treatment of snakebites in communities that lack prompt access to serum therapy. However, the identification and characterization of the effects of several new plants or their isolated compounds, which are able to inhibit the activities of snake venom, are extremely important and such studies are imperative. Snake venom contains several organic and inorganic compounds; phospholipases A2 (PLA2 s) are one of the principal toxic components of venom. PLA2 s display a wide variety of pharmacological activities, such as neurotoxicity, myotoxicity, cardiotoxicity, anticoagulant, hemorrhagic, and edema-inducing effects. PLA2 inhibition is of pharmacological and therapeutic interests as these enzymes are involved in several inflammatory diseases. This review describes the results of several studies of plant extracts and their isolated active principles, when used against crude snake venoms or their toxic fractions. Isolated inhibitors, such as steroids, terpenoids, and phenolic compounds, are able to inhibit PLA2 s from different snake venoms. The design of specific inhibitors of PLA2 s might help in the development of new pharmaceutical drugs, more specific antivenom, or even as alternative approaches for treating snakebites.